Digital Literation Development and Assembly for Increasing the Quality of Youth in Using the Internet - D. Claretta; Y. Candasari; Sumardjijati (Nusantara Science and Technology Proceedings)
The teenagers in Gunungsari village, Bumiaji sub-district, since the age of 9 years have known the internet. They already have a smartphone and use the gadget without any guidance and assistance from their parents, most of whom are farmers and farm workers with a low level of education. The dropout rate is quite high as a result of the increasing unemployment rate and immoral issues have surfaced in the life of Gunungsari people since their children got to know the internet. This condition shows the low digital literacy of parents, so the second problem is that teenagers in Gunungsari village do not have Individual competence in using digital media. The purpose of this community service program is to apply the results of digital literacy research and mentoring youth in using digital media in a healthy way and how mothers can assist children in using the internet in a healthy manner. The results obtained from the Digital Literacy training in adolescents who are adolescents of Gunungsari village are able to protect their privacy in cyberspace and teenagers can have good digital literacy. Whereas in the Mother group, digital literacy has been achieved even though at the basic stage, it is around the issue of how to protect children from dependence on the internet and the mothers have downloaded applications that can be used to protect children.